Characteristics Associated With Disparities Among Older Adults in Coronavirus Disease 2019 Outcomes in an Academic Health Care System. Issue 5 (1st May 2022) - Gelfman, Laura P.; Moreno, Jaison; Frydman, Julia L.; Singer, Joshua; Houldsworth, Jane; Cordon-Cardo, Carlos; Mehrotra, Meenakshi; Chai, Emily; Aldridge, Melissa; Morrison, Rolfe S.
Abstract : Background: An improved understanding of the coronavirus disease 2019 (COVID-19) pandemic is needed to identify predictors of outcomes among older adults with COVID-19. Objective: The objective of this study was to examine patient and health system factors predictive of in-hospital mortality, intensive care unit (ICU) admission, and readmission among patients with COVID-19. Design, Setting, and Participants: A cohort study of patients aged 18 years and older with COVID-19 discharged from 5 New York hospitals within the Mount Sinai Health System (March 1, 2020–June 30, 2020). Measures: Patient-level characteristics (age, sex, race/ethnicity, comorbidities/serious illness, transfer from skilled nursing facility, severe acute respiratory syndrome coronavirus 2 viral load, Sequential Organ Failure Assessment score, treatments); hospital characteristics. Outcomes: All-cause in-hospital mortality; ICU admission; 30-day readmission. Results: Among 7556 subjects, mean age 61.1 (62.0) years; 1556 (20.6%) died, 949 (12.6%) had an ICU admission, and 227 (9.1%) had a 30-day readmission. Increased age [aged 55–64: odds ratio (OR), 3.28; 95% confidence interval (CI), 2.41–4.46; aged 65–74: OR, 4.67; 95% CI, 3.43–6.35; aged 75–84: OR, 10.73; 95% CI, 7.77–14.81; aged 85 y and older: OR, 20.57; 95% CI, 14.46–29.25] and comorbidities (OR, 1.11; 95% CI, 1.16, 2.13) were independent risk factors for in-hospital mortality. Yet older adults (aged 55–64 y: OR, 0.56; 95% CI, 0.40–0.77; aged 65–74: OR, 0.46; 95% CI, 0.33–0.65; aged 75–84: OR, 0.27; 95% CI, 0.18–0.40; aged above 85 y: OR, 0.21; 95% CI, 0.13–0.34) and those with Medicaid (OR, 0.74; 95% CI, 0.56–0.99) were less likely to be admitted to the ICU. Race/ethnicity, crowding, population density, and health system census were not associated with study outcomes. Conclusions: Increased age was the single greatest independent risk factor for mortality. Comorbidities and serious illness were independently associated with mortality. Understanding these risk factors can guide medical decision-making for older adults with COVID-19. Older adults and those admitted from a skilled nursing facility were half as likely to be admitted to the ICU. This finding requires further investigation to understand how age and treatment preferences factored into resource allocation.